Medical planning (leaflet) - British Medical Association; Lucas Young, A.
1943-07 1943 1940s 7 pages 5. Would you be prepared to see your doctor at a Health Centre instead of at his private house provided appointments could be fixed in order to avoid waiting? 6. Do you think that the elimination of the competitive element from medical practice would have a good effect or the the reverse? 7. Do you consider that a patient's financial status should have any bearing on the treatment available? 8. The relationship of doctor and patient is necessarily a very personal one. Do you think there would be any danger of this relationship being impaired if your doctor became a salaried servant of the State instead of an independent worker? Your opinion on any relevant points not covered in the above questions would be welcomed. Your replies will be treated as strictly confidential and will not be associated with your name in any conclusions arrived at the organising committee. R. M. BARRON, DAPHNE DEAR, P. W. MATHEW, A. LUCAS YOUNG (Hon. Sec.), Public Relations Committee July, 1943. British Medical Assocn. 292/847/2/107